Legal Protection for Gig Workers: A New Business Imperative in the Transportation Sector - Abdullah, Nurhidayah; Murad, Muhammad Syariqul Huzni; Kunhibava, Sherin; Mahdzir, Nazli; Abd Ghadas, Zuhairah Ariff (Yuridika, 2025)
Studies on the gig economy and the legal status of its workers have proliferated in recent years. However, there is still much to be learned about how to regulate this relatively new job market. The government has made efforts to support e-hailing and p-hailing workers, particularly regarding social security. For example, they introduced a voluntary contribution plan under the Employees' Provident Fund for retirement savings and the Self-Employment Social Security Scheme, which offers some protections for work-related injuries. Despite these efforts, they appear to be insufficient and ineffective due to the absence of an appropriate regulatory body overseeing these workers' issues. This article argues for the imperative need for a governing legal framework to address e-hailing and p-hailing workers' rights and prevent Platform Providers from exploiting workers' livelihoods due to the absence of laws. The research employs both doctrinal and qualitative research methods, including interviews using a semi-structured approach. A total of 10 respondents were interviewed for this research. The findings suggest that a solid legal framework, including specific laws and regulatory bodies, is essential to govern the e-hailing and p-hailing ecosystem.